Hormonal response to Taekwondo fighting simulation in elite adolescent athletes - Pilz-Burstein, R.; Ashkenazi, Y.; Yaakobovitz, Y.; Cohen, Y.; Zigel, L.; Nemet, D.; Shamash, N.; Eliakim, A. (European Journal of Applied Physiology, 2010)
Exercise training efficiency depends on the training load, as well as on the athlete`s ability to tolerate it. The aim of the present study was to evaluate the effect of fighting simulation (3 fights, 6 min each, 30 min rest between fights) on anabolic (IGF-I, LH, FSH, estradiol, and testosterone) and catabolic hormones (cortisol) in elite, male (n = 10) and female (n = 10) adolescent (12-17 years) Taekwondo fighters. Blood samples were collected before the first and immediately after the third fight. The fighting simulation practice led to significant (p < 0.05) decreases in IGF-I (males -27.1 ± 25.6, females -22.4 ± 36.3 ng/ml), LH (males -0.7 ± 1.2, females -2.3 ± 3.3 U/L), and FSH (males -0.9 ± 0.5, females -1.5 ± 1.1 U/L), and to a significant increase (p < 0.05) in cortisol (males 141.9 ± 30.1, females 64.1 ± 30.6 mcg/dL) in both genders. Fighting simulation decreases in testosterone (males -1.9 ± 1.6, females -0.02 ± 0.06 ng/mL), and free androgen index (males -20.1 ± 21.5, females -0.3 ± 0.5) were significant (p < 0.05) only in male fighters. Exercise had no significant effect on estradiol, sex-hormone-binding globulins or thyroid function tests. Our data demonstrate that the physiologic and psychologic strain of a Taekwondo fighting simulation day led to a catabolic-type circulating hormonal response.